MELUMPUHKAN TINDAK PIDANA PENCUCIAN UANG DENGAN HUKUM PIDANA ISLAM - Ismail Marzuki (Wajah Hukum, 2018)
The phenomenon of money laundering crime (money laundering) lately more andmore the case. Because through the channel of money laundering, the perpetrators increasingly exist run many actions a crime. This is due to the material or their proceeds of crime property as the spirit of the live action wicked behavior they can be hidden with a neat, and can be put to good use because it looked legitimate sourced. These conditions if left, certainly much cause any harm to society. Moreover, if such money laundering crimes reviewed philosophically in Islamic law (Sharia ash-trends). Regard posed obvious greater than maslahahnya. Therefore, the outstanding strategies needed to cripple or eradicate the behaviour a criminal offence of money laundering.Keywords: Money Laundering, Islamic Law, Eradication Strategies